ABSORBER DESIGN SIMULATION FOR CO2 USING K2CO3 ABSORBENT WITH ASPEN HYSYS V.10 SOFTWARE - Chusnul Chotimah; Naja Nikmah Syafitri; Kartika Udyani (Konversi, 2022)
An absorber is a tool used in the absorption process to separate a certain gas component from a gas mixture using a chemical solution as an absorbent. This simulation aimed to determine the effects of the packing type and column diameter on flooding, the packing type and column diameter on pressure drop, and the gas flow rate on CO2 removal. It also investigated the best absorber design based on %flooding and pressure drop. This simulation was carried out using the Aspen Hysys software version V.10. The variables of packing type consisted of PALL, berl, and raschig. The simulation results indicated that the larger the column diameter for each type of packing, the smaller the %flooding value. Meanwhile, the limit value of the %flooding for each type of packing given by Aspen Hysys was 30%– 80%. Further simulation results showed that the larger the column diameter in each type of packing, the smaller the pressure drop value. The pressure drop limit value given by Aspen Hysys was 3,658 mbar. In addition, the next simulation results demonstrated that the greater the value of the given gas flow rate, the greater the % CO2 removal value. Thus, the effective absorber design viewed from the %flooding and pressure drop was a 0.5-inch berl dimension with ceramic material. Keywords: absorber, type of packing, flooding, pressure drop, CO2 removai